La prévalence des tendinopathies de la coiffe des rotateurs à la consultation du rhumatologie au niveau de la polyclinique Gallouma Miloud durant la période (01 juin 2021 – 31 janvier 2023). - SELT Hibat Errahman Fatna; TIAIBA Souad (Université Amar Télidji Laghouat, 2023)
Introduction : Rotator cuff tendinopathy is a very common pathology in general medicine, rheumatology and orthopedics. The objective of our study was to evaluate the prevalence of rotator cuff tendinopathies in the rheumatology consultation at the Gallouma Miloud polyclinic during the period (June 2021 – January 2023). Method : This is an observational, descriptive, retrospective epidemiological study on rheumatology consultation files at the Gallouma Miloud polyclinic. The study is carried out over a period of twenty (20) months from 06/01/2021 to 01/31/2023. Results : This analysis of the clinical files made it possible to conclude that : -The average age of the patients was 57.12 years. -A clear predominance of women with a sex ratio (F / H) of 11.5. -The most injured shoulder was the left shoulder. -The most frequent reason for consultation was the association of pain with the limitation of movements. -The ultrasound was the X-ray examination that makes it possible to make the positive diagnosis. -The supraspinatus tendon was the most affected tendon. -Simple tendinopathy was the common condition in our study population. -Analgesics, NSAIDs and corticosteroid infiltrations constituted the first therapeutic component.
30cm CD-ROM